(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This article studies the semantic features of hydronyms, toponyms with a zoomorphic component, and ethnotoponyms in German and Uzbek languages. The similarities in naming the place names of the German and Uzbek peoples are considered.